Zoledronic acid in lung cancer with bone metastases: a review. Issue 4 (April 2013) - Isla, Dolores; Afonso, Ruth; Bosch-Barrera, Joaquim; Martínez, Natividad
Lung cancer remains the leading cause of cancer mortality worldwide and bone metastases develop in approximately 30–40% of cases. Bisphosphonates are a key therapy for bone metastases; zoledronic acid is the only bisphosphonate with efficacy in preventing, reducing the incidence and delaying the onset of skeletal-related events controlling bone pain. Several bone metabolism markers indicate bone resorption activity, linking with prognosis and efficacy of zoledronic acid. Zoledronic acid has a well-established tolerability profile and can be administered safely as long-term therapy, although preventive measures are needed to avoid some severe side effects (nephrotoxicity and osteonecrosis of the jaw) found in a small number of patients receiving long-term therapy. Currently, lung cancer patients with bone metastases are candidates to receive zoledronic acid in clinical practice with demonstrated benefits and safety preserving quality of life. Additional roles in anticancer activity deserve attention and are under investigation.